Cuerpos que (no) importan y nuevas alianzas - Marta Segarra (Mélanges de la Casa de Velázquez)
Based on Judith Butler’s theories on the body (Bodies That Matter), this paper reflects on how some beings are relegated to the external margins of the community and reduced to an anonymous mass, which is often more related to animality than to humanity. From an ecofeminist and posthuman perspective (especially as developed by Cary Wolfe and Donna Haraway), it also examines the possibility of a reformulation of the human community beyond the «family», through new «modes of intimate alliance», Butler’s definition of «kinship».